Individual'nye razlichija kak osnova optimizacii sportivnoj dejatel'nosti - Salnikov, V. A. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The steadfast attention, devoting to the problem of an individualization of training is caused by the aspiration to the optimization of managerial processes by the sports training. The individualization of the sports activity from the point of view of the system approach is represented as the system of conformity of the pedagogical influences to the specific features of the age development. The author comes to the conclusion, that it is important to overcome the gap between abstract orientation to the person, existing in the pedagogical theory, and the practice of the training and competitive process with the modeling approach, specific for it, and insufficiently deep penetration into the essence of personal and individual displays. In result, it turns around to the interest in the organization by the external side of the influence, due to a lot of available methodical approaches.